Komposisi dan Keanekaragaman Vegetasi di Saluran Irigasi pada Lahan Pertanian Desa Mulya Sari Kabupaten Banyuasin - Wiwik Septiani; Siti Masreah Bernas; Yuanita Windusari (Jurnal Penelitian Sains, 2017)
Mulya sari village of Banyuasin regency is the one of sub-optimal area with tidal swamp land and characteristic sulfit acid. Its have an impact on paddy fields stagnancy, and brought environment problems. The presence of aquatic vegetation abundant and diversified in irrigation canals can be waste water reduction. The purpose of this research is to know diversity of aquatic vegetation on irrigation canals of Mulya Sari Vil-lage. Methode that used in this research is survey methode with purposive sampling. Observation and mea-surement data capture done in may 2016. From the research found as many as 7 species type of vegetation aquatic from 3 types class. First class from Liliopsida as many as 3 type, second class from Monocotyledonae as many as 3 type, and third class from Dicotiledonae just 1 type. Structure of vegetation diversity is very low classified with value about 0,57 – 1,57. The results of studies also show that water quality and sediment charac-ter of the irrigation canals. According to goverment regulation No. 82 in the year 2001 that compatible with natural characteristic, water quality include not polluted until heavy polluted. The results of structure soil frac-tion research, the dominant diversity is silt soil fraction.